Perception of young local residents toward sustainable conservation programmes: A case study of the Lenggong World Cultural Heritage Site - Jaafar, Mastura; Md Noor, Shuhaida; Rasoolimanesh, Mostafa S. (ELSEVIER, 2015)
This paper examines the relationships between the perception of young local residents regarding tourism development and conservation efforts, their involvement in promoting and supporting Lenggong Valley as a World Heritage Site (WHS), and their sense of belonging. This paper also asks if the involvement of young residents in activities to support the WHS acts as a mediator of their perceptions and their sense of belonging. A questionnaire survey was administered to all Y4 and Y5 students from three secondary schools in Lenggong Valley. A total of 175 completed questionnaires were returned. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was applied to the resultant data using SmartPLS 2.0 software. The results revealed that having positive perceptions had a positive effect on young residents' involvement in promoting and supporting the Lenggong WHS. A positive relationship between young residents' negative perceptions and their sense of belonging was also found. These findings indicate that involvement plays a mediating role in the relationship between residents' positive perceptions and their sense of belonging. The findings contribute to our understanding of the importance of youth perceptions in pursuing sustainable tourism development and in planning WHS conservation programmes. Our findings might also be relevant to Lenggong's local authorities wanting to increase the involvement of local residents, in particular youth, in supporting and promoting the status of the WHS and in enhancing their sense of belonging.